2022
DOI: 10.3390/pr10081506
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Organic Carbon and Physical Health of Structurally Disturbed Soil through Microbe–Manure Amalgam

Abstract: Less precipitation, high temperature, and minimal natural vegetation are characteristic of regions having an arid climate. The harsh environment massively destructs the soil structure of that area by burning soil organic carbon, leading to deteriorated soil nutritional quality, creating a significant threat to agricultural production and food security. Direct application of organic wastes not only substitutes lost organic carbon but also restores soil structure and fertility. This study was conducted to assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 65 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Lim et al (2015) found the same things we did. Organic matter in the soil is essential because it enhances the soil's chemical, physical, and biological properties, all of which contribute to its overall quality (Gondal et al, 2021b(Gondal et al, , 2022aJiang et al, 2022). That's why compost, with its nutritional and organic matter content, makes for a great organic fertiliser.…”
Section: Discussionmentioning
confidence: 99%
“…Lim et al (2015) found the same things we did. Organic matter in the soil is essential because it enhances the soil's chemical, physical, and biological properties, all of which contribute to its overall quality (Gondal et al, 2021b(Gondal et al, , 2022aJiang et al, 2022). That's why compost, with its nutritional and organic matter content, makes for a great organic fertiliser.…”
Section: Discussionmentioning
confidence: 99%
“…Sleumer, three treatments (formulations) were carried out, with 3 repetitions each, the quantities are described in Table 1. Based on the results of the one-way analysis of variance (ANOVA), we employed a completely randomized design (CRD) with three repeats to compare the means of the treatments (Younas et al, 2022;Jiang et al, 2022;Gondal et al, 2023b), employing the TUKEY test with a 95% confidence interval…”
Section: Process Of Obtaining the Drinkmentioning
confidence: 99%
“…For example, in Bangladesh, the farmers took advantage of heavily discounted chemical fertilizers and pesticides (Umetsu, 2022). Moreover, the leading causes of crops' low yield are late planting, improper plant spacings and planting methods, shallow sowing, pest and disease management, insufficient fertilizer uses, delayed harvesting, and adopting low-yielding cultivars (Jiang et al, 2022;Gondal et al, 2023).…”
Section: Introductionmentioning
confidence: 99%